2008
DOI: 10.1080/15548730802118215
|View full text |Cite
|
Sign up to set email alerts
|

Rural Families' Connections to Services in an Alternative Response System

Abstract: Alternative response systems, which address low-risk cases of child maltreatment, are based on three assumptions: that services are available, that services are accessible, and that service networks develop to connect families to services. This article examines whether the nature of rural areas challenges these assumptions. Findings from a qualitative study of families' connections to services in alternative response systems conducted in an urban and rural county in two states, Oklahoma and Kentucky, suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Most studies of differential response systems have focused on specific states and have identified some positive effects on child safety/recidivism, family engagement and satisfaction, provision of services, and social worker satisfaction (Child Welfare Information Gateway, 2008; Zielewski & Macomber, 2007). Among the most extensively studied state systems are Missouri, Minnesota and North Carolina (Waldfogel, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies of differential response systems have focused on specific states and have identified some positive effects on child safety/recidivism, family engagement and satisfaction, provision of services, and social worker satisfaction (Child Welfare Information Gateway, 2008; Zielewski & Macomber, 2007). Among the most extensively studied state systems are Missouri, Minnesota and North Carolina (Waldfogel, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One factor that may affect the success of differential response initiatives is the underlying assumption that if CPS identifies family needs, effective community services to address these needs are readily available (Zielewski & Macomber, 2007). Where services are not adequate or accessible, CPS identification of family needs will not be sufficient to set families on a path toward better outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transportation issues were particularly acute in the rural counties (Zielewski & Macomber, 2007;Zielewski et al, 2006).…”
Section: Service Provision and Differential Responsementioning
confidence: 99%
“…Findings also suggested that increased contact with CPS worker and increased length of service delivery contributed to decreased re-reporting (Siegel & Loman, 2006). Zielewski and Macomber (2007) noted that DR systems are based on assumptions that services are available and accessible and that families connect to services through service networks. A small study of DR in one urban and one rural county each in Oklahoma and Kentucky identified service network infrastructure, service availability, referral and follow-up processes, approaches to families, and service facilitators as factors that could affect families' connections to services (Zielewski, Macomber, Bess, & Murray, 2006).…”
Section: Service Provision and Differential Responsementioning
confidence: 99%